2005
DOI: 10.1086/466518
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation in NGC 5194 (M51a): The Panchromatic View fromGALEXtoSpitzer

Abstract: Far ultraviolet to far infrared images of the nearby galaxy NGC 5194 (M51a), from a combination of space-based (Spitzer, GALEX, and Hubble Space Tele-1 Based on observations obtained with the Spitzer Space Telescope and with GALEX.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
563
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(637 citation statements)
references
References 97 publications
68
563
6
Order By: Relevance
“…Offsets and anti-correlations between FUV and 12 CO (or FIR and Hi) emissions have also been seen in other spiral galaxies such as M 100 (Rand 1995;Sempere & García-Burillo 1997;Calzetti et al 2005), M 51 (Calzetti et al 2005), and NGC 3147 (Casasola et al 2008a). These anti-correlations may relate to star formation efficiency and timescale variations in response to a spiral density wave.…”
Section: Far-ultraviolet Morphologymentioning
confidence: 74%
“…Offsets and anti-correlations between FUV and 12 CO (or FIR and Hi) emissions have also been seen in other spiral galaxies such as M 100 (Rand 1995;Sempere & García-Burillo 1997;Calzetti et al 2005), M 51 (Calzetti et al 2005), and NGC 3147 (Casasola et al 2008a). These anti-correlations may relate to star formation efficiency and timescale variations in response to a spiral density wave.…”
Section: Far-ultraviolet Morphologymentioning
confidence: 74%
“…As part of SINGS (Spitzer Infrared Nearby Galaxies Survey, Kennicutt et al (2003)), Spitzer obtained high-resolution IR maps of a large sample of nearby galaxies. Calzetti et al (2005) and Calzetti et al (2007) demonstrated the utility of these maps to trace recently formed stars obscured on small scales, particularly when used in combination with Hα -a tracer of unobscured star formation.…”
Section: Recent Advances: Gas and Star Formation On Sub-kiloparsec Scmentioning
confidence: 99%
“…The 8 µm mid-infrared emission is generally considered to trace the PAHs heated by UV photons (Leger & Puget 1984;Sellgren 1984). It is thought that 2/3 of the 8 µm emission from a galaxy originates from heating by stellar populations 100 Myr or younger (Calzetti et al 2005;Calzetti 2013), and that PAH emission is stronger for increasing metallicity and dust content of the interstellar medium (e.g., Engelbracht et al 2005;Marble et al 2010;Calzetti 2013). The 24 µm emission is generally produced by dust following absorption of UV photons emitted by young stars, and traces SF on a time scale of 10 Myr (Calzetti et al 2005;Leroy et al 2008).…”
Section: Ancillary Optical and Infrared Imagesmentioning
confidence: 99%
“…It is thought that 2/3 of the 8 µm emission from a galaxy originates from heating by stellar populations 100 Myr or younger (Calzetti et al 2005;Calzetti 2013), and that PAH emission is stronger for increasing metallicity and dust content of the interstellar medium (e.g., Engelbracht et al 2005;Marble et al 2010;Calzetti 2013). The 24 µm emission is generally produced by dust following absorption of UV photons emitted by young stars, and traces SF on a time scale of 10 Myr (Calzetti et al 2005;Leroy et al 2008). In this paper we use archival 3.6 µm, 8 µm and 24µm images from Fazio et al (2004) obtained with the Infrared Array Camera and The Multiband Imaging Photometer on the Spitzer Space Telescope (Rieke et al 2004;Werner et al 2004).…”
Section: Ancillary Optical and Infrared Imagesmentioning
confidence: 99%
See 1 more Smart Citation